Bezpieczeństwo Polski w drugiej dekadzie XXI wieku: przegląd dotychczasowych działań i dalszych wyzwań - Koziej, Stanisław (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2016)
The second decade of the 21st century is an important period for building Polish security. This is due to rapid developments in the international environment (Russian – Ukrainian military conflict, activity of the so-called Islamic State), as well as the changing domestic political situation which brings about not only strategic but also systemic transformations. This situation makes it necessary to analyse the changing threats and needs as well as an evaluate and forecast strategic moves made by Poland in the field of security. Hence, the article reviews and evaluates conditions and actions that Poland undertakes to shape its national security and outlines main tasks that need to be carried out in order to strengthen it in the next years.
Keywords: the Komorowski doctrine; security strategy; NATO; defence policy; EU Common Security and Defence Policy; modernization; Polish Military Forces; national security system; concept of deterrence; information security; the USA